Autosomal recessive primary microcephaly in sibs in time of Zika epidemic: a Case Report - Almeida, Julia V.; Abdala, Bianca Barbosa; Rabelo, Natana Chaves; Gomes, Maria Eduarda; Ferreira Bastos, Elenice; Llerena, Juan Clinton; Gonzalez, Sayonara (Frontiers in Genetics, 2025)
Case report of two siblings, born to consanguineous parents, with congenital microcephaly secondary to a pathogenic homozygous ASPM gene variant. The proband was born during the Zika virus epidemic with a prenatal history of maternal exanthematous disease. Genetic diagnosis was made after the birth of the sibling, born with a similar condition. Next-generation sequencing enables a definitive diagnosis in cases of microcephaly, and genetic diagnosis should be pursued even when the patient history points to a possible, but not definite, environmental cause. Conclusive genetic diagnosis allows for precise and timely family planning and counseling.